2005
DOI: 10.4028/www.scientific.net/ssp.106.87
|View full text |Cite
|
Sign up to set email alerts
|

Wavelength Tunable Random Laser

Abstract: Continuously tunable random laser basing on rhodamine 6G was achieved. Wavelength tuning was implemented by wedge-shaped sample shift relatively to the pump beam. The physical base of the tuning method is gain band shift caused by reabsorption. We ascertained that two medium thickness ranges of significantly different tune efficiency exist. The lasing characteristics of the laser were investigated depending on active medium and pump beam parameters. The feedback formation mechanisms in the random lasers of dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…6,7 However, in the field of random lasing [8][9][10][11] both absorption and multiple scattering of light are essential ingredients. 8,[14][15][16] In a convincing series of recent experiments, Gottardo et al 17 have shown that Mie resonances can shift the peak wavelength of a random laser by a few line widths. The gain curve of the emission molecules is the main mode selection mechanism in a random laser.…”
Section: Tuning Random Lasers By Engineered Absorptionmentioning
confidence: 99%
“…6,7 However, in the field of random lasing [8][9][10][11] both absorption and multiple scattering of light are essential ingredients. 8,[14][15][16] In a convincing series of recent experiments, Gottardo et al 17 have shown that Mie resonances can shift the peak wavelength of a random laser by a few line widths. The gain curve of the emission molecules is the main mode selection mechanism in a random laser.…”
Section: Tuning Random Lasers By Engineered Absorptionmentioning
confidence: 99%